Applying the TPB and the UTAUT Models Predicting Intentions to Use Telemedicine Among Thai People During the COVID-19 Pandemic - Siripipatthanakul, Supaprawat; Limna, Pongsakorn; Sriboonruang, Patcharavadee; Kaewpuang, Pichart (International Journal of Computing Sciences Research, 2023)
Purpose – This study applied the theory of planned behaviour (TPB) model and the unified theory of acceptance and use of technology (UTAUT) model to predict intentions to use telemedicine among Thai people during the COVID-19 pandemic. Method – The TPB model predictors of intentions to use telemedicine included attitude, subjective norm, and perceived behavioural control. The UTAUT predictors of intentions to use telemedicine included performance expectancy, effort expectancy, and facilitating conditions. The data were gathered using convenience sampling among 213 respondents collected through self-administered online questionnaires. The conceptual framework was examined with the Partial Least Squares Structural Equation Modelling (PLS-SEM), adopting the ADANCO software program (version 2.3) and SPSS (version 27). Results – The empirical findings showed the relationship between predictors and intentions to use telemedicine during the COVID-19 pandemic among Thai people. The results revealed that performance expectancy strongly influences attitude, followed by subjective norm and perceived behavioural control. But attitude is not a significant mediator between antecedents of effort expectancy, subjective norm, perceived behavioural control and intentions to use telemedicine. Moreover, performance expectancy has the most influence on intentions to use telemedicine, followed by facilitating conditions and effort expectancy. Conclusion – The healthcare strategic planners should pay attention to performance expectancy, facilitating conditions and effort expectancy because these factors impact intentions to use telemedicine among Thai people. Recommendations –The recommendation is to consider a qualitative study in further study for more insight results to explain the relationship phenomenon among UTAUT, TPB model, and intentions to use telemedicine. Implication – The implication benefits other sectors that could apply the UTAUT model to enhance the behavioural intention of customers and citizens.